2017
DOI: 10.3892/ol.2017.6901
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin induces cell apoptosis in human chondrosarcoma cell line SW1353 via inhibition of the PI3K/Akt signaling pathway

Abstract: Abstract. Chondrosarcoma is a malignant soft tissue sarcoma with poor prognosis. Puerarin has been demonstrated to possess anticancer properties; however, the effects of puerarin in human chondrosarcoma cells remain unknown. The present study aimed to investigate the anticancer effects of puerarin in SW1353 human chondrosarcoma cells. SW1353 cells were treated with increasing concentrations of puerarin for different durations. Cell viability was evaluated using MTT assays. Cell apoptosis rates were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…The results of the present study indicate that Puerarin significantly suppressed PI3K, p-Akt and p-mTOR protein expression in HeLa HPV-18 positive cervical cancer cells, thereby reducing their proliferative and migration abilities; however, PI3K upregulation reduced the anticancer effect of Puerarin on HeLa cells. Huang et al (13) revealed that Puerarin induces cell apoptosis in human chondrosarcoma cells via inhibition of the PI3K/Akt signaling pathway, which supports the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the present study indicate that Puerarin significantly suppressed PI3K, p-Akt and p-mTOR protein expression in HeLa HPV-18 positive cervical cancer cells, thereby reducing their proliferative and migration abilities; however, PI3K upregulation reduced the anticancer effect of Puerarin on HeLa cells. Huang et al (13) revealed that Puerarin induces cell apoptosis in human chondrosarcoma cells via inhibition of the PI3K/Akt signaling pathway, which supports the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Puerarin has strong pharmacological activity (12) and a wide range of pharmacological effects, including anti-arrhythmia, anti-myocardial infarction, anti-angiectasis, antitumor, microcirculation improvement, blood fat reduction, increased cerebral blood flow, protection against oxidation, regulation of bone metabolism and reduction of intraocular pressure (11,12). Huang et al (13) demonstrated that Puerarin induces cell apoptosis in human chondrosarcoma cells via inhibiting the PI3K/Akt signaling pathway. The aim of the present study was to explore the effects of Puerarin on apoptosis in HPV-positive cervical cancer cells and the molecular mechanisms responsible.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphoinositide 3-kinase (PI3K), a member of the phospholipid kinase family, serves important roles in the regulation of the apoptosis, proliferation, differentiation and metabolism of cells (9). The serine-threonine protein kinase Akt is a downstream target of PI3K; when stimulated by extracellular signals, PI3K-activated Akt initiates a cascade of intracellular reactions (10). PI3K is composed of a regulatory subunit (p85) and a catalytic subunit (p110), and activation of the catalytic subunit depends upon the phosphorylation of p85 (11).…”
Section: Introductionmentioning
confidence: 99%
“…miR-155 mimic (100 ng), miR-155 inhibitor (100 ng) and negative control (100 ng) were transfected into cells using Lipofectamine 2000 (Thermo Fisher Scientific, Inc.). Following transfection for 6 h, the medium was removed and fresh medium was added, containing 0.1 ng/ml human interleukin (IL)-4 (Sigma-Aldrich; Merck KGaA), 1 ng/ml human tumor necrosis factor (TNF)-α (Sigma-Aldrich; Merck KGa A) a nd 10 ng/m l huma n inter feron ( I F N )-Îł (Sigma-Aldrich; Merck KGaA) for 24 h. Cells were then cultured as keratinocyte-induced HacaT cells, an in vitro model for psoriasis, as previously reported in the literature (14). cells were induced with 100 ng/ml LPS (Beyotime Institute of Biotechnology, Jiangsu, china) for 24 h. cells were treated with NLRP3 inhibitor, Mcc950 (2 nM; MedChemExpress, Shanghai, China) for 8 h.…”
Section: Methodsmentioning
confidence: 99%